Cuarenta y cinco songs: on poems of Goethe and Eichendorff for voice and piano - Wolf, Hugo. 1860-1903 (Dover art songs & lieder, 1995)
In his relatively brief life, German composer Hugo WOlf (1860-1903) created one of the great legacies in the art of song. Among his most deeply affecting works are his settings of poems by Johann Wolfgang von Goethe and Joseph von Eichendorff. This volume contains 45 of these songs, reprinted fron authoritative German editions.